Clinical presentation and outcome of Graves disease in pediatric patients with and without type 1 diabetes: a retrospective cohort study - Wu, Yi-Hsin; Wang, Lu-Ting; Lee, Yann-Jinn; Huang, Chi-Yu; Kao, Yu-En; Lin, Chao-Hsu; Cheng, Bi-Wen; Lo, Fu-Sung; Ting, Wei-Hsin (Frontiers in Endocrinology, 2025)
IntroductionType 1 diabetes (T1D) is associated with autoimmune thyroid disease (AITD). However, few studies have explored the clinical presentation and outcomes of Graves disease (GD) in T1D patients. In this study, we examined the clinical manifestation and compared the remission rates of GD in pediatric patients with and without T1D.Materials and MethodsPatients with T1D diagnosed at ≤ 18 years at MacKay Children’s Hospital, Taipei, from 2000 to 2020 underwent annual screening for AITD. Those who met the criteria for GD were enrolled in the study. Clinical manifestations, demographic data, thyroid function test results, methimazole dosage and outcome data were collected and compared with those pediatric GD patients without T1D.ResultsOf the 651 pediatric patients with T1D, 15 (2.3%) developed GD either with or after their T1D diagnosis. At the time of GD diagnosis, 11 of 15 GD patients with T1D (73.3%), and 98.9% patients without T1D exhibited symptoms of thyrotoxicosis, indicating a significant difference (p < 0.001). GD patients with T1D had significantly lower median free T4 levels (2.2 vs. 4.1 ng/dL, p < 0.001) and TSH receptor antibody (TRAb) (27.2% vs. 58.5%, p = 0.004) compared with those patients without T1D.Following treatment, free T4 levels normalized more rapidly in GD with T1D group (2.2 vs. 3.5 months, p = 0.031) with a lower dosage of methimazole (0.1 vs. 0.33 mg/kg/day, p < 0.001). However, no significant difference was observed in remission rate (33.3% vs. 23.4%, p = 0.377) or time to remission (3.3 vs. 4.5 years, p = 0.446) between the two groups.ConclusionThe prevalence of GD in children and adolescents with T1D was 2.3%. Compared with GD patients without T1D, those with T1D exhibited fewer thyrotoxic symptoms and had lower free T4 and TRAb levels at the time of GD diagnosis. Although the remission rate did not significantly differ between the two groups, annual screening for GD should still be considered because it assisted in the rapid relief of thyrotoxicosis with relatively low dosage of antithyroid drugs.